Disharmoni Regulasi Perkawinan Siri di Indonesia: Antara Penegakan Pidana dan Celah Administratif - Ahmad Faiz Shobir Alfikri; Maziya Rahma Wahda; Ahmad Zulfi Wahyudi (Prodi Ahwal Asy Syahsiyah, Fakultas Syariah dan Hukum, Universitas PTIQ Jakarta, 2026)
The practice of unregistered marriage (nikah siri) in Indonesia remains widespread despite the state’s long-standing obligation to register marriages under the Marriage Law. This article examines two interrelated issues: the position of Article 404 of the new Criminal Code as an affirmation of the marriage registration obligation and its underlying philosophy of legal protection, and the synchronization between administrative population policy and the protective spirit of marriage registration law. This research employs a normative legal method with a statutory and conceptual approach, analyzing primary legal materials comprising the Marriage Law, the new Criminal Code, the Ministerial Regulation on Population Administration, the Compilation of Islamic Law, and the Indonesian Ulema Council Fatwa Number 10 of 2008. The findings reveal that Article 404 of the new Criminal Code constitutes a normative affirmation and instrumental reinforcement of Article 2 paragraph (2) of the Marriage Law, transforming what was previously a declarative obligation into an enforceable legal duty grounded in utilitarian punishment theory aimed at protecting women and children from the adverse effects of unregistered marriage. However, this normative reinforcement is undermined by the Ministerial Regulation on Population Administration, which accommodates unregistered marriages through the “not yet registered marriage” mechanism, thereby creating a regulatory inconsistency. This inconsistency reflects a philosophical incoherence in the state’s approach to unregistered marriage, threatening legal certainty and weakening the effectiveness of legal protection for women and children within the institution of marriage in Indonesia.